Tindak Tutur (Speech Act) dan Implikatur dalam Penggunaan Bahasa - Paulana Christian Suryawin; Maryadi Wijaya; Heri Isnaini (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The language and context of speech cannot be separated from each other, the two intertwine in tandem and complement each other. The communication process uses language as a medium for conveying its message. Communicators (speakers), communicants (speakers), messages, and speech situations are necessary parts of communication that are expected to be smooth communication and the delivery of messages. The delivery of the message by the speaker becomes hampered when there is a misalignment of understanding received by the speaker. This is what pragmatics is trying to interpret. Pragmatics is the study of the relationship of language to its context. In a comprehensive understanding of language in communication will give birth to language functions that ultimately form a strong language character. It is presented in the article on speech acts and implicature in the use of language.